"Small steps, or giant leaps?" Comparing game demands of U23, U18, and U16 English academy soccer and their associations with speed and endurance. Issue 1 (February 2022) - Smalley, Ben; Bishop, Chris; Maloney, Sean J
The current study aimed to compare locomotive outputs across English U16, U18 and U23 academy soccer and investigate possible relationships with neuromuscular and aerobic capacities. Participants included 46 outfield players from an English Category Two soccer academy. Global positioning system (18 Hz) data were utilised to analyse locomotive outputs across twenty eleven-a-side matches in each age group. Maximal sprinting speed (MSS) and aerobic speed (MAS) were assessed at the beginning of the season. Absolute total distance (TD), high-speed running (HSR), acceleration and deceleration workloads were higher in U18's and U23's vs. U16's (g = 1.09–2.58; p < 0.05), and absolute sprinting distances were higher in U23's vs. U16's (g = 0.96; p < 0.05). In addition, relative HSR outputs were higher in U23's vs. U18's (g = 1.84–2.07; p < 0.05). Across the whole cohort, players' MSS was positively associated with absolute HSR and sprinting distances (ρ = 0.53–0.79; p < 0.05) but not with relative parameters. MAS was positively associated with total distance, decelerations, and both absolute and relative HSR outputs (ρ = 0.33–0.56; p < 0.05). Overall, absolute locomotive outputs were significantly higher in U23's and U18's vs. U16's. Locomotive outputs were also associated with maximal sprinting and aerobic speeds. Thus, training programmes should be tailored to competition demands to optimally prepare each age group for competition and reflect the increasing demands of each level of competition. Further, improving physical fitness (speed and endurance) is likely to drive greater outputs in competition.